DNA methylation pattern in high-grade cervical intraepithelial neoplasia and cancer revealed by genome- wide methylation analysis of cervical DNA. Issue 5 (2017) - García, D Adriana; Abba, Martin C; Briceño, Ignacio; Aristizabal, Fabio A; Arregui, Angel Cid
No abstract available